Biotécnicas de proteção de taludes em aterros urbanos - PEREIRA JUNIOR, Clodomir Barros (2015)
The study proposes actions to evaluate, on a pilot scale, the performance of biotech in the conservation and protection of slopes, in the neighborhood of Dois Irmãos in the city of Recife, Pernambuco, contributing to the development of a technology to be used in the conservation of the urban slopes, that meet the legal requirements and techniques aims to assess the soil shear resistance in different types of soil covers the experiment was composed of 21 plots, of which 16 were selected experimental plots consist of four types, which were subjected to four repetitions, which represented four types of coverages that may be adopted in the recovery of degraded areas. This work aimed to evaluate the shear strength in experimental plots with 2.0 m wide by 5.0 m in length, using different types of toppings: (1) sediment retainers on bare soil; (2) biomanta of sisal fiber; (3) grass Vetiver Vetiveria zizanioides L (Nash), randomized; (4) soil without vegetation cover. The chance to be verified is that different types of toppings and combinations contribute to maximize soil shear resistance, aiding in conservation and slope protection in municipal landfills. The products are based on the results obtained and noting that the typologies used in grassy coverage obtained more shear strength than bare soil.